WEE1 Inhibition in Combination With Targeted Agents and Standard Chemotherapy in Preclinical Models of Pancreatic Ductal Adenocarcinoma - Hartman, Sarah J.; Bagby, Stacey M.; Yacob, Betelehem W.; Simmons, Dennis M.; MacBeth, Morgan; Lieu, Christopher H.; Davis, S. Lindsey; Leal, Alexis D.; Tentler, John J.; Diamond, Jennifer R.; Eckhardt, S. Gail; Messersmith, Wells A.; et al. (Frontiers in Oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal cancer with high incidences of p53 mutations. AZD1775 (adavosertib, previously MK-1775) is a small molecule WEE1 inhibitor that abrogates the G2M checkpoint and can potentially synergize with DNA damaging therapies commonly used in PDAC treatment. The purpose of this study was to identify combination partners for AZD1775, including standard chemotherapy or targeted agents, in PDAC preclinical models. Low powered preliminary screens demonstrated that two of the four PDX models responded better to the combinations of AZD1775 with irinotecan or capecitabine than to either single agent. Following the screens, two full powered PDAC PDX models of differing p53 status were tested with the combinations of AZD1775 and irinotecan or capecitabine. The combinations of AZD1775 and SN38 or 5-FU were also tested on PDAC cell lines. Cellular proliferation was measured using an IncuCyte Live Cell Imager and apoptosis was measured using a Caspase-Glo 3/7 assay. Flow cytometry was conducted to measure alterations in cell cycle distribution. Western blot analysis was used to determine the effects of the drug combinations on downstream effectors. In PDX models with mutated p53 status, there was significant tumor growth inhibition from the combination of AZD1775 with irinotecan or capecitabine (P ≤ 0.03), while PDX models with wild type p53 did not show anti-tumor synergy from the same combinations (P ≥ 0.08). The combination of AZD1775 with SN38 or 5-FU significantly decreased proliferation in all PDAC cell lines, and enhanced apoptosis in multiple cell lines. Cell cycle distribution was disrupted from the combination of AZD1775 with SN38 or 5-FU which was recorded as G2M arrest and decreased G1 phase. AZD1775 inhibited phospho-CDC2 and increased the expression of γH2AX that was either maintained or enhanced after combination with SN38 or 5-FU. The combination of AZD1775 with irinotecan/SN38 or capecitabine/5-FU showed anti-tumor effects in vivo and in vitro in PDAC models. These results support further investigation for these combination strategies to enhance outcomes for PDAC patients.